A prospective study on physical performance of Chinese chronic obstructive pulmonary disease males with type 2 diabetes. Issue 35 (3rd September 2021) - Liu, Junhong; Song, Xiao; Zheng, Shuangshuang; Ding, Hui; Wang, Honggang; Sun, Xicai; Ren, Xiangfeng
Abstract : Abstract: Currently no research is available on muscle and functional performance of chronic obstructive pulmonary disease (COPD) patients with type 2 diabetes (T2DM) in China, even though both diseases have been reported to damage motor function. This single-center prospective study involves 55 males with COPD and T2DM and 46 males with COPD. Lung function, muscle strength and endurance of the upper limbs, and quadriceps strength of both legs were assessed using instruments. The 6-min walk (6MW) test was performed to evaluate physical performance. Between the two groups, respiratory function of COPD patients with T2DM was worse than in those without ( P  < .05). Mean handgrip strength and muscle endurance of upper limbs and mean quadriceps strength at both 60°/s and 120°/s in COPD males with T2DM was also significantly less ( P  < .05). Mean 6MW distances of COPD patients with T2DM were significantly worse ( P  < .05), and mean pulse rate (PR) increments of COPD patients with T2DM in 6MW test were significantly higher ( P  < .05). The combination of COPD and T2DM not only brings one more chronic disease to elderly patients but also significantly affects muscle strength and endurance as well as physical performance. Accordingly, in the management of chronic diseases, we recommend that clinicians as well as patients themselves actively control blood sugar and review them regularly with a view to reducing adverse effects on physical performance.